2017
DOI: 10.1177/1179573517726335
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Dopamine D3Receptor Signaling in the Diseased Brain

Abstract: Dopamine D3 receptors (D3R) modulate neuronal activity in several brain regions including cortex, striatum, cerebellum, and hippocampus. A growing body of evidence suggests that aberrant D3R signaling contributes to multiple brain diseases, such as Parkinson’s disease, essential tremor, schizophrenia, and addiction. In line with these findings, D3R has emerged as a potential target in the treatment of neurological disorders. However, the mechanisms underlying neuronal D3R signaling are poorly understood, eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 107 publications
2
27
0
Order By: Relevance
“…In the DRD3 , the Gly9 variant of the Ser9Gly polymorphism changes D3 receptor density (Jeanneteau et al, 2006; Prieto, 2017). Consequently, the impact of this variant concerning antipsychotics response has been widely investigated (Arranz et al, 2011; Reynolds, 2012a; Brandl et al, 2014), but as with other receptor genes, such as DRD1, DRD4, DRD5 , inconclusive findings have been obtained (Hwang et al, 2010; Brandl et al, 2014; Lally et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the DRD3 , the Gly9 variant of the Ser9Gly polymorphism changes D3 receptor density (Jeanneteau et al, 2006; Prieto, 2017). Consequently, the impact of this variant concerning antipsychotics response has been widely investigated (Arranz et al, 2011; Reynolds, 2012a; Brandl et al, 2014), but as with other receptor genes, such as DRD1, DRD4, DRD5 , inconclusive findings have been obtained (Hwang et al, 2010; Brandl et al, 2014; Lally et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several evidence have emerged supporting other activation models than the classical one, including observations that (1) GPCRs can form either hetero- or homodimers and create functional pre-coupled complexes with heterotrimeric G proteins in the rest state (Han et al, 2009; Parker et al, 2011; Ferre et al, 2014; Nishimura et al, 2017; Prieto, 2017; Durdagi et al, 2018; Navarro et al, 2018; Tóth et al, 2018; Calebiro and Koszegi, 2019); (2) the G proteins can exist in a pre-coupled complex with the GPCR and an effector protein, as AC; further, binding of agonists to GPCR might result in the activation of the G protein without its dissociation from the complex (Ferré, 2015; Navarro et al, 2018); (3) some G α subunits can interact and modulate downstream signaling even when bound to GDP (Kamakura et al, 2013; Lin et al, 2014); (4) newly identified modulators of G protein activity, called GEMs (guanine exchange modulators), can activate and inhibit different G α subunits through the same motif (Gupta et al, 2016; Ghosh et al, 2017).…”
Section: Heterotrimeric G Proteins Of the Gi/o Subfamilymentioning
confidence: 99%
“…Several pieces of evidence link the dopamine D 3 receptor to SUD. First, expression of dopamine D 3 receptors is increased in several brain areas from cocaine abusers, metamphetamine users and alcohol dependent patients (for reviews (Prieto, 2017;Sokoloff and Le Foll, 2017). Second, the Ser9Gly polymorphism known to enhance ERK signaling and to be responsible for essential tremor has also been linked to early onset of heroin dependence in Han Chinese subjects (Kuo et al, 2014).…”
Section: Dopamine D 3 /D 3nf Heteromersmentioning
confidence: 99%